Síntese, caracterização e aplicações biomédicas de nanopartículas magnéticas - Britos, Tatiane Nassar [UNIFESP] (2014)
In the development of this work were performed syntheses and morphological characterization - structural and magnetic - of iron oxide nanoparticles and the Fe3O4 metal type (Fe0) which were obtained from the thermodecomposition and coprecipitation methods, respectively, and biological assays. The surfaces of these nanoparticles were functionalized with thiolated binders and hydrophilic (-SH), with the aim of making these biocompatible systems to act as carriers of nitric oxide (NO) and contrast agents in magnetic resonance imaging. Fe3O4 nanoparticles, such as magnetite, were synthesized by coprecipitation method, starting from FeCl3.6H2O FeCl2.4H2O salts and in acid medium. In a first step the surfaces of these nanoparticles were coated with a hydrophobic binder, such as oleic acid, in order to avoid clumping and to be subsequently exchanged for biocompatible thiolated binders and as mercaptosuccínico acid (MSA) and cysteine (Cys) Fe3O4 in mole ratios: MSA / Cys 1:40 to 1:20. Nanoparticles of Fe3O4-type MSA and Fe3O4-Cys were obtained with the direct coating their surfaces also. This second preparation step was conducted aiming to the optimization of the method of synthesis. Fe0 nanoparticles were synthesized by the method of the organometallic precursor thermodecomposition as iron III acetylacetonate [Fe(acac)3]. The thiolated nanoparticles were nitrosadic by sodium nitrite salt in a slightly acid, leading to the formation of magnetic systems nitric oxide donors (-SNO). These nanoparticles were characterized by a number of physicochemical techniques for verification of the structural, morphological and magnetic aspects and were tested as carrier of nitric oxide in culture of tumor cells and as contrast agents for stem cells also. The results showed that thiolated nanoparticles are crystalline, spherical and with narrow size distribution and showed superparamagnetic behavior. In addition, nitric oxide acts as a carrier for the treatment of cancer cells and as contrast agents for stem cells in magnetic resonance imaging.